1996
DOI: 10.1177/096032719601500314
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine compounds in human brain

Abstract: Having observed polychlorinated biphenyls (PCBs) in brain tissue obtained post mortem from two men we have carried out a study of organochlorine compounds in frontal cortex from patients with Parkinson's disease (PD) and from controls. No PCBs were found in any of those samples. There was no difference in the concentra tion of the DDT metabolite pp'-DDE in the PD brain samples. Dieldrin (HEOD) was significantly decreased in PD brain when analysed by lipid weight. While these findings would not support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 10 publications
(5 reference statements)
1
26
0
Order By: Relevance
“…Research over the last several decades has provided a wealth of support for exposure to environmental chemicals, including organochlorine insecticides as a risk factor for PD (Hatcher et al , 2008). Indeed, levels of organochlorine compounds, such as dieldrin and β-HCH have been found to be elevated in the brain tissue and serum, respectively, of PD patients and have been shown in laboratory studies to damage the nigtrostriatal dopamine system (Corrigan et al , 1996; Corrigan et al , 2000; Kitazawa et al , 2001; Kitazawa et al , 2004; Hatcher et al , 2007; Richardson et al , 2009; Richardson et al , 2011). In addition to these compounds, a recent epidemiological study also identified exposure to the organochlorine insecticide, endosulfan, as a risk factor for PD (Rhodes et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research over the last several decades has provided a wealth of support for exposure to environmental chemicals, including organochlorine insecticides as a risk factor for PD (Hatcher et al , 2008). Indeed, levels of organochlorine compounds, such as dieldrin and β-HCH have been found to be elevated in the brain tissue and serum, respectively, of PD patients and have been shown in laboratory studies to damage the nigtrostriatal dopamine system (Corrigan et al , 1996; Corrigan et al , 2000; Kitazawa et al , 2001; Kitazawa et al , 2004; Hatcher et al , 2007; Richardson et al , 2009; Richardson et al , 2011). In addition to these compounds, a recent epidemiological study also identified exposure to the organochlorine insecticide, endosulfan, as a risk factor for PD (Rhodes et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Available epidemiological studies point towards an increased risk associated with insecticides (in particular organochlorine insecticides; Elbaz et al 2009;Freire & Koifman 2012) and herbicides (Pezzoli & Cereda 2013). Interestingly, the epidemiological evidence for the involvement of organochlorine insecticides is underlined by biomarkers of exposure in serum (Weisskopf et al 2010) and post mortem detection of elevated levels of particular organochlorine insecticides in brains of PD patients (Corrigan et al 1996;Corrigan et al 2000).…”
Section: The Role Of Pesticides In Pdmentioning
confidence: 99%
“…Thus, human exposure to dieldrin continues via contaminated food (Corrigan et al, 1996). Studies indicate that exposure to dieldrin is closely associated with Parkinson's disease (Fleming et al, 1994;Corrigan et al, 2000).…”
mentioning
confidence: 99%